2022
DOI: 10.3390/joitmc8020099
|View full text |Cite
|
Sign up to set email alerts
|

The FDI Spillover Effect on the Efficiency and Productivity of Manufacturing Firms: Its Implication on Open Innovation

Abstract: In this study, we investigated the effects of foreign direct investment (FDI) spillovers on firm production and technical efficiency in Indonesia’s manufacturing sector from 2010 to 2015. We scrutinized three different channels of horizontal spillover, namely, demonstration, technology adoption, and competition channels. We also captured the heterogeneous effect of firms by categorizing them based on their technological intensity (low, medium, or high). Using time-varying stochastic production frontier analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 66 publications
1
16
0
1
Order By: Relevance
“…Recently Sugiharti et al [25] investigated the effects of FDI spillovers on output and productivity in Indonesia's manufacturing industry from 2010 to 2015. Results revealed that FDI benefits all technological groups through productivity and efficiency improvement, with hightech firms seeing the most benefit because they have a strong ability to adopt the technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Sugiharti et al [25] investigated the effects of FDI spillovers on output and productivity in Indonesia's manufacturing industry from 2010 to 2015. Results revealed that FDI benefits all technological groups through productivity and efficiency improvement, with hightech firms seeing the most benefit because they have a strong ability to adopt the technology.…”
Section: Introductionmentioning
confidence: 99%
“…Importing higher-quality materials often necessitates more human resources, which can enhance TFP. Similarly, import activities in the context of technology allow firms to gain access to higher technologies, which is more viable because they may not have the resources to conduct their research and development (Sugiharti et al, 2022).…”
Section: Analysis Of Control Variables: Fdi Wages Trade Openness and ...mentioning
confidence: 99%
“…Recent studies have scrutinized the channels that facilitate externalities (FDI spillovers) to local economies, such as demonstration, competition, knowledge, and labor mobility. The first three channels have received increasing attention and have been examined by Esquivias and Harianto (2020), Sugiharti et al (2022), Sari et al (2016), and Suyanto et al (2014). Meanwhile, labor mobility, which captures how knowledge is transferred through informal exchanges between workers, has not been extensively researched.…”
Section: Introductionmentioning
confidence: 99%
“…MNCs can also have a spillover effect on non-FDI recipient firms in the sector and region where they operate in the form of knowledge, managerial practices, know-how and technological sharing. The transmission of knowledge, practices and technology from MNCs is through labor mobility, demonstration and competition (Sugiharti et al , 2022).…”
Section: Introductionmentioning
confidence: 99%